(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Phytotherapy is an inevitable companion of human civilization. Smilax wightii is an ethnomedicinal plant in Smilacaceae, with unexplored scientifically therapeutic potential. The antihyperglycemic, antioxidant and hepatoprotective capabilities of the methanolic extract of leaf, stem, rhizome and root of S. wightii were inspected in the present study. Hyperglycemia is a manifestation of the prevalent metabolic disorder, Type 2 Diabetes mellitus. Inhibitors of α –glucosidase and α – amylase could be efficiently employed in diabetes mellitus therapy as hypoglycemic agents. In the α –glucosidase and α – amylase inhibitory assays, root and rhizome extracts recorded better antihyperglycemic activity. DPPH radical scavenging activity and total antioxidant capacity were the parameters employed to determine the antioxidant activity. Hepatoprotectivity determines the capability of samples to safeguard the hepatocytes from damage. Novel hepatoprotective agents are in demand since the incidence of liver impairment is on a high among global population. The rhizome extract showed comparatively superior hepatoprotectivity followed by the leaf, stem and root extracts. Rhizome, at 100μg/ml guaranteed a cell viability percentage of 77.43 in the Chang liver cell line treated with Carbon tetrachloride. So the root and rhizome of S. wightii are the therapeutically significant plant parts with hypoglycemic, free radical scavenging and hepatoprotective potentialities.